Inuit women’s attitudes and experiences towards cervical cancer and prevention strategies in Nunavik, Quebec - Cerigo, Helen; Macdonald, Mary Ellen; Franco, Eduardo L.; Brassard, Paul (Taylor & Francis, 2012)
To describe the attitudes about and experiences with cervical cancer, Pap smear screenings and the HPV vaccine among a sample of Inuit women from Nunavik, Quebec, Canada. We also evaluated demographic and social predictors of maternal interest in HPV vaccination. [.]